Testing scenarios on geological models: Local interface insertion in a 2D mesh and its impact on seismic wave simulation. (February 2022) - Legentil, Capucine; Pellerin, Jeanne; Cupillard, Paul; Froehly, Algiane; Caumon, Guillaume
Abstract: In this work, we propose a local updating method to test different contact depth scenarios and assess their impact on wave propagation in the subsurface. We propose to locally modify a 2D geological model and run time-dependent elastic simulations. The input model triangulation is conforming to geological structures. The 2D meshed model is locally updated, which means that only the reservoir compartment is modified. Several model geometries are generated by inserting a new interface, in this paper a gas–water contact that is defined by a scalar field. We quantitatively evaluate the impact of the gas–water contact depth on elastic wave propagation. We run the numerical simulations with Hou10ni2D code, which is based on a Discontinuous Galerkin method. The simulation results are compared to a reference depth by computing the L2-norm at a set of seismic receivers. Results show a consistent behavior: we observe a positive correlation between the depth difference and global L2-norm for all receivers. This approach could therefore be integrated into an inversion loop to determine the position of the fluid contact and reduce uncertainties in the reservoir model from a few seismic sensors. The algorithms are available on Github and distributed under a GPL license, allowing reproducibility. Highlights: An approach to locally insert interfaces in triangular meshes for simulations. The local insertion preserves mesh conformity. An assessment of the detectability of fluid contacts in reservoirs with seismic waves.